Identification Of The AT III Synthesizing Hepatocytes By Immunofluorescent Technique - Watada, M; Nakagawa, M; Kitani, T; Okajima, Y; Maeda, Y; Urano, S; Ijichi, H (Thrombosis and Haemostasis, 1981)
Antithrombin III (AT III), heparin cofactor has been known to be one of the important protease inhibitors on the regulatory mechanism of coagulation and fibrinolysis, but the site of synthesis of plasma AT HI has not yet been conclusively established, although some observations suggested that the major site of AT III production may be the liver and AT III levels in plasma is known to be decreased on the hepatic disorders. This paper reports the deposition of the AT III specific fluorescence in the hepatocytes of rat liver by immunofluorescent examination. Plasma AT III was purified by heparin sepharose affinity chromatography and gel filtrations. Rabbit was immunized with this purified AT III and Freund’s complete adjuvant and rabbit anti rat AT III serum was obtained. This antiserum was comfirmed to be monospecific to rat AT HI by means of immunoelectrophoresis. Freshly isolated rat liver was prepared as specimen and fixed in acid alcohol and processed to dehydration and embedding into paraffin in conventional way. Indirect immunofluorescent technique with FITC labeled anti rabbit gamma-globulin were utilized for immunofluorescent staining and histological observation was performed under Nikon FL fluorescent microscope. The localization of fluorescence was observed in the hepatocytes which scattered in the acinus structures. The fluorescence in the cytoplasma of these hepatocytes was homogeneously stained. As far as the fluorescence is concerned, the synthesis of AT III may be performed not synchronizing among hepatocytes. This immunofluorescent study supports the reported data of hepatic perfusion.